2001
DOI: 10.1159/000049733
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Soluble Adhesion Molecules in Acute Pancreatitis

Abstract: The relationship between inflammatory cytokines and adhesion molecules in cases of acute pancreatitis was studied. Twenty-five patients were divided into three groups based on the severity of their disease as rated by the Ranson score. They were also divided into two groups according to the presence or absence of the complications of the multiorgan dysfunction syndrome (MODS) and the prognosis. As the severity of acute pancreatitis increased, the plasma levels of TNF-α, slCAM-1, sE-selectin, and sVCAM-1 also i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Moreover, during 3 days from admission, E-selectin concentrations were increasing in severe disease in contrast to mild AP [132]. Nakae et al [133] observed positive correlation between soluble E-selectin and TNF-α in the early phase of human AP; both mediators were positively associated with AP severity. Hynninen et al [134] reported similarly increased soluble E-selectin in patients with SAP and with severe sepsis, positively correlated with SOFA scores.…”
Section: Laboratory Markers Of Endothelial Activation and Injury Imentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, during 3 days from admission, E-selectin concentrations were increasing in severe disease in contrast to mild AP [132]. Nakae et al [133] observed positive correlation between soluble E-selectin and TNF-α in the early phase of human AP; both mediators were positively associated with AP severity. Hynninen et al [134] reported similarly increased soluble E-selectin in patients with SAP and with severe sepsis, positively correlated with SOFA scores.…”
Section: Laboratory Markers Of Endothelial Activation and Injury Imentioning
confidence: 99%
“…In this study, strong positive correlations were observed between plasma-soluble ICAM-1 and severity of organ dysfunction (APACHE III and SOFA scores) in SAP patients. Nakae et al [133] observed higher soluble ICAM-1 in patients who died from AP than in survivors.…”
Section: Laboratory Markers Of Endothelial Activation and Injury Imentioning
confidence: 99%
See 1 more Smart Citation
“…Acute pancreatitis causes a release of various inflammatory mediators, attracts inflammatory cells to the vascular endothelium and induces the expression of adhesion molecules (1,24). Studies have shown that NF-κB plays a critical role in the development of acute pancreatitis (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in acute pancreatitis and severe burn, serum levels of sICAM-1 and sVCAM-1 have been shown to reflect the severity of the disease and be associated with the prognosis [5,6]. …”
Section: Introductionmentioning
confidence: 99%